2020
DOI: 10.31557/apjcp.2020.21.6.1499
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of JC and BK viruses in Patients with Colorectal Cancer: A Systematic Review and Meta- Analysis

Abstract: Introduction: Polyomaviruses including BK virus (BKV) and JC virus (JCV) are widespread in human and have been associated with colorectal cancer (CRC) in some studies. The aim of present systematic review and meta-analysis article is to calculate the pooled prevalence of BKV and JCV in patients with CRC and assessing their association with this malignancy. Materials and Methods: Domestic databases and Sciences Direct, PubMed, ProQuest, Web of Sciences and Scopus were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…Additionally, JCV infection increased the odds for colorectal adenoma development (6-fold) more than colorectal cancer (4.1-fold). Our findings corroborate the results of recent meta-analyses indicating that the presence of JCV in colorectal tissues increased the odds of colorectal tumors by 4.4 to 4.7 times compared to the absence of the virus [50,51] . In these studies, however, colorectal cancer and adenoma were not looked at individually, and the association of JCV infection with EO-CRC was not assessed.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, JCV infection increased the odds for colorectal adenoma development (6-fold) more than colorectal cancer (4.1-fold). Our findings corroborate the results of recent meta-analyses indicating that the presence of JCV in colorectal tissues increased the odds of colorectal tumors by 4.4 to 4.7 times compared to the absence of the virus [50,51] . In these studies, however, colorectal cancer and adenoma were not looked at individually, and the association of JCV infection with EO-CRC was not assessed.…”
Section: Discussionsupporting
confidence: 91%
“…Herpesviridae HHV7 Oral HHV7 DNA frequently detected in oral cavity cancer [26] HSV (HHV1/2) Oral Higher proportion of HSV-positive oral squamous cell carcinoma in industrialized countries [41] KSHV (HHV8) Kaposi sarcoma In HIV-infected individuals, KSHV infection is associated with Kaposi sarcoma [42] Polyomaviridae BKV Bladder Possible association of BKV with bladder cancer [26] BKV Colorectal Possible association of BKV with colorectal cancer [43,44], however, other studies found no association [16,45] JCV Colorectal…”
Section: Virus Family Virus Cancer Type Observationsmentioning
confidence: 99%
“…JCV T antigen was involved in colorectal carcinogenesis and liver metastasis ( Sinagra et al, 2014 ; Shoraka et al, 2020 ; Vilkin and Niv, 2011 ). Reportedly, JCV T antigen stabilized β-catenin for its nuclear translocation to initiate cancer proliferation and development ( Nosho et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%